Penerapan Auto Feeder dan Sistem Monitoring Kualitas Air Real-Time Berbasis Tenaga Surya pada Budidaya Minapadi Terintegrasi POKDAKAN Kridoyuwono, Panembangan, Banyumas - Sukardi, Purnama; Anjaini, Jefri; Lilik Setiyaningsih; Nur Alfi Ekowati; Agung Tri Nugroho; Frentina Murti Sujadi; Asro Nurhabib; Baruna Kusuma; Yohannes Harvinda; Kholilah Nur Hidayah; Dandi Setio Wibowo; Dimas Yoland Dewantio (Jurnal Pengabdian Magister Pendidikan IPA, 2025)
Panembangan Village has strong potential for rice–fish culture (minapadi) but faces constraints in feeding efficiency, unmonitored water quality, and dependence on grid electricity. This community‐service program offers an integrated solution: an IoT-based auto feeder combined with real-time water-quality monitoring (DO, pH, temperature, conductivity/TDS, turbidity) and powered by off-grid solar energy (PV) to ensure continuous operation. The primary goal was to improve feed efficiency, enhance fish growth, reduce feed waste, and optimize water quality management in aquaculture systems. The implementation of these technologies has demonstrated significant improvements in feed conversion ratios, growth rates of fish, and overall water quality management. The program also provided training to local farmers, enhancing their capacity to manage these technologies effectively. This initiative is expected to contribute to the sustainable development of aquaculture in the region, benefiting both the local community and the environment